Diagnostic and prognostic role of electrocardiogram in acute myocarditis: A comprehensive review. Issue 3 (28th November 2019) - Buttà, Carmelo; Zappia, Luca; Laterra, Giulia; Roberto, Marco
Abstract: Background: Acute myocarditis represents a challenging diagnosis as there is no pathognomonic clinical presentation. In patients with myocarditis, electrocardiogram (ECG) can display a variety of non‐specific abnormalities. Nevertheless, ECG is widely used as an initial screening tool for myocarditis. Methods: We researched all possible ECG alterations during acute myocarditis evaluating prevalence, physiopathology, correlation with clinical presentation patterns, role in differential diagnosis, and prognostic yield. Results: The most common ECG abnormality in myocarditis is sinus tachycardia associated with nonspecific ST/T‐wave changes. The presence of PR segment depression both in precordial and limb leads, a PR segment depression in leads with ST segment elevation, a PR segment elevation in aVR lead or a ST elevation with pericarditis pattern favor generally diagnosis of perimyocarditis rather than myocardial infarction. In patients with acute myocarditis, features associated with a poorer prognosis are: pathological Q wave, wide QRS complex, QRS/T angle ≥ 100°, prolonged QT interval, high‐degree atrioventricular block and malignant ventricular tachyarrhythmia. On the contrary, ST elevation with a typical early repolarization pattern is associated with a better prognosis. Conclusions: ECG alterations in acute myocarditis could be very useful in clinical practice for a patient‐tailored approach in order to decide appropriate therapy, length of hospitalization, and frequency of followup.